PWE-181 Quantitative Assessment Of Global Small Bowel Motility In Chronic Intestinal Pseudo-obstruction And Controls: A Preliminary Study. (9th June 2014) - Butt, SK; Menys, A; Atkinson, D; Plumb, A; Taylor, S; Zarate-Lopez, N; Emmanuel, A
Abstract : Introduction: In this preliminary report, we present the initial results of a prospective investigation comparing MRI quantified global small bowel motility in healthy controls and patients with proven clinical and radiological Chronic Intestinal pseudo-obstruction (CIPO). Diagnosis is initially difficult and often delayed, many patients undergoing unnecessary surgical intervention prior to final diagnosis. MRI offers a potential non-invasive modality of diagnosis and monitoring, employing post-processing quantitation of global metrics describing small bowel motility 1 . Methods: Subject selection: 11 healthy non-smoking volunteers (7 Male, mean age 33[22 to 48]) and 5 CIPO patients (3 Male, mean age 53[32 to 82]) were recruited. CIPO patients stopped any medications that influenced small bowel motility for one week prior to scan including opioids, anti-emetics and anti-diarrhoeals. Study overview: Participants underwent a single MRI motility scan before and immediately after an injection of 0.5 mg IV neostigmine, a cholinomimetic with potent prokinetic action. Statistics: Data normality was assessed using Shapiro-Wilk testing. 1) Baseline motility was compared in CIPO patients and controls. 2) Percent change in motility between baseline and post-neostigmine was compared between groups. Difference in means were tested using Welch's T-test. Results: Mean baseline small bowel motility scores in CIPO patients was 0.19AU (range 0.1 to 0.25) and in controls 0.35AU (range 0.275 to 0.37) with a statistically significant difference of 0.17AU, P = 0.0026 (CI 0.09 to 0.23). The mean percent increase in small bowel motility scores in CIPO patients following noestigmine was 29% (95% CI from 19 to 50%) and in controls 10% (range 0 to 34) with a statistically significant difference in groups response to neostigmine of 19%, P = 0.029 (95% CI from 4 to 40%). Conclusion: This study demonstrated significant differences in both resting and cholinomimetic-induced global motility between CIPO patients and healthy controls. Despite marked bowel distension in the CIPO patients, motility appeared present but reduced compared to controls, and responded to provocation with neostigmine suggesting the bowel still exhibits the expected pro-kinetic effects following pharmacological stimulation. With just five patients this is a preliminary study, nevertheless initial results appear promising and support our ongoing investigation program. Reference: 1 Menys et al . Global Assessment Radiol 2013;269(2):443-50 2 Odille et al . Qu, UKantitative assessment MRM 2012;68(3):783-93 Disclosure of Interest: None Declared.